Macroeconomic determinants of stock market liquidity: Evidence from selected Asian emerging markets / Ijaz Ur Rehman - Ijaz , Ur Rehman (2016)
The popularization of commonalities in liquidity has led the stock market liquidity research to encompass a broader spectrum to investigate the role of macroeconomic forces. Previous stock liquidity literature that uses macroeconomic factors to examine their influence on market liquidity is focused on developed -liquid markets- and quote-driven stock markets. Little is known about the market liquidity sensitivity toward the macroeconomy in Asian emerging equity markets, which are mostly order-driven. This study therefore examines whether macroeconomic variables and stock market liquidity affect each other in five Asian emerging markets, namely, China, India, Pakistan, Malaysia, and Thailand. In particular, this study addresses three major objectives. First is to examine the role of macroeconomic variables in explaining market liquidity in the selected Asian emerging markets. Second is to compare the role of macroeconomic forces in market liquidity of selected Asian emerging markets. Third is to investigate causality/reverse causality/feedback effect between market liquidity and macroeconomic variables in the selected Asian emerging markets. This study uses monthly macroeconomic and stock market illiquidity measures over the period of January 2000 to December 2014 and therefore, employs three kinds of analysis. To address the first and second objective, this study first examines the long and the short run impact of macroeconomic variables on stock market illiquidity using Vector Error correction Models. The results suggest that policy rate and foreign equity flow/fund flow explain stock market illiquidity in four selected Asian emerging markets. In regards to the business cycle components, real economic activities explain stock market illiquidity in three Asian emerging markets in the long run. In the short run, concerning the monetary policy variables, both the monetary base and the policy rate have a lagged effect on stock market illiquidity in the three out of five selected Asian emerging markets. Concerning the business cycles components, inflation has a lagged effect on stock market illiquidity in the four Asian emerging markets while foreign equity flow/fund flow has significant lagged effect on stock market illiquidity in four Asian emerging markets in the short run. To address the third objective, this study used Granger causality analyses. The results of Granger causality analyses suggest that monetary base and policy rate cause stock market illiquidity in three and one Asian emerging market, respectively, while real economic activities and inflation cause stock market illiquidity in four and one Asian emerging markets respectively. Foreign equity flow/fund flow causes stock market illiquidity in four Asian emerging markets. The causality analysis further suggests that there is bidirectional causality between foreign inflow, inflation, and stock market illiquidity in the Thailand and the Bombay equity markets. The Innovative Accounting Approach (IAA) is used to check the robustness, direction, feedback, extent, and relative strength of casual relationship ahead of selected time span. The results of Innovative Accounting Approach (IAA) suggest that positive shock to policy rate and inflation increases stock market illiquidity in few selected Asian emerging markets while negative shock to monetary base and foreign equity flow/fund increases stock market illiquidity in two out of the total number of selected Asian emerging markets. The results of IAA further suggest that positive shock to real economic activities decreases stock market illiquidity in the majority of Asian emerging markets. The results of variance decomposition analysis (VDA) suggest that business cycle components contribute more to stock market illiquidity in two Asian emerging markets while monetary base has more contribution in stock market illiquidity in the case of Bombay stock exchange and foreign equity flow/fund flow has more contribution in three Asian emerging equity markets. The VDA further suggests that there is feedback effect between foreign equity flow/fund and stock market illiquidity in the case of Thailand stock market and the Bursa Malaysia. The implications of the findings are also presented.